2017
DOI: 10.1155/2017/6853212
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytochemical Profiling and In Vitro Antioxidant Activity of Extracts from Raw Materials, Tissue‐Cultured Plants, and Callus of Oroxylum indicum (L.) Vent.

Abstract: Extracts from raw materials from different plant parts, tissue-cultured plants, and callus cultures of Oroxylum indicum were analyzed for in vitro antioxidant activities determined by DPPH radical scavenging assay and evaluated for phytochemical profiles by TLC and LC-MS methods. The results were analyzed by principal component analysis (PCA) to evaluate the similarity. Stalk, pedicel, flower, seed, and whole fruit and callus extracts promoted strong antioxidant activity with high total phenolic and total flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…This study also supports the previous experiment as simvastatin was treated as a very potential lipid-lowering drug and coincided with prior studies [102][103][104][105][106]. To identify the level enzymes (both SGPT and SGOT) both treatment protocols failed to decrease the level of specific enzyme level to a noteworthy extent and exhibited similarities with past studies [107][108][109][110][111][112][113] but revealed satisfactory decline. Liver enzymes SGPT and SGOT are considered as surrogate markers of diabetes mellitus complication.…”
Section: Discussionsupporting
confidence: 89%
“…This study also supports the previous experiment as simvastatin was treated as a very potential lipid-lowering drug and coincided with prior studies [102][103][104][105][106]. To identify the level enzymes (both SGPT and SGOT) both treatment protocols failed to decrease the level of specific enzyme level to a noteworthy extent and exhibited similarities with past studies [107][108][109][110][111][112][113] but revealed satisfactory decline. Liver enzymes SGPT and SGOT are considered as surrogate markers of diabetes mellitus complication.…”
Section: Discussionsupporting
confidence: 89%
“…Baicalin, baicalein, and chrysin exhibited antibacterial effects on the tested bacteria, in which baicalin promoted the highest inhibitory effects, suggesting it is the main active compound [15]. These three flavonoids were also tested for DPPH scavenging effects, in which baicalin and baicalein showed strong free radical scavenging activities, while chrysin promoted a low inhibitory effect [17]. The explanation about the lower antibacterial effects of the seeds ethanol and water extracts of O. indicum, which contained higher baicalin contents, but promoted lower antibacterial effects than the young fruit ethanol extract that contain lower baicalin content, was that the fixed oil in the seeds of O. indicum could interfere with the antibacterial effect of the seed extracts [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation about the lower antibacterial effects of the seeds ethanol and water extracts of O. indicum, which contained higher baicalin contents, but promoted lower antibacterial effects than the young fruit ethanol extract that contain lower baicalin content, was that the fixed oil in the seeds of O. indicum could interfere with the antibacterial effect of the seed extracts [15,18]. Extracts from O. indicum tissue-cultured plants in early stages (day 5, day 7, week 2, and week 3) were reported to contain high total phenolic contents (higher than 5 g% GAE) with moderate amounts of total flavonoids (around 1-2 g% QE), while extracts from the late stages of tissue-cultured plants (week 4-week 8) promoted lower total phenolic and total flavonoid contents (1-4 g% GAE, and cannot be detected −3 g% QE, respectively) [17]. In our current study, the root of the tissue-cultured plant was developed at day 4, while the cotyledons and true leaves were developed at weeks 3 and 9, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations